2021
DOI: 10.1515/jcim-2019-0341
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of methanol extract of Annona muricata stem bark on mitochondrial membrane permeability transition pore in normal rat liver and monosodium glutamate-induced uterine hyperplasia

Abstract: Objectives Uterine fibroids are benign tumors that develop in many women of reproductive age. Surgery is the main approach to treatment while other options are also associated with adverse effects. Studies have shown that certain bioactive agents present in medicinal plants elicit their anti-tumor activity by induction of mitochondrial permeability transition (mPT) opening. This research therefore aimed at investigating the effect of methanol extract of Annona muricata (MEAM) on mPT pore open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Experimental evidences have shown that some phytochemical compounds elicit their chemopreventive and antiproliferative effects by triggering mPT pore opening. These include betulinic acid (Yong et al 2013), Drymaria cordata (Olowofolahan et al 2015), Calliandria portoricensis (Oyebode et al 2017), Mangifera indica (Olowofolahan et al 2018), and etc. Metformin is an anti-diabetic drug used for the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidences have shown that some phytochemical compounds elicit their chemopreventive and antiproliferative effects by triggering mPT pore opening. These include betulinic acid (Yong et al 2013), Drymaria cordata (Olowofolahan et al 2015), Calliandria portoricensis (Oyebode et al 2017), Mangifera indica (Olowofolahan et al 2018), and etc. Metformin is an anti-diabetic drug used for the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%